Judas Rose - Elgin, Suzette Haden (Book collections on Project MUSE., 2019)
"In the second book of the Native Tongue trilogy, a small group of women linguists have developed a women's language, Láadan, but their resistance is threatened by a group of priests who uncover their plan to spread the language throughout the world."--